MHC-I pathway disruption by viruses: insights into immune evasion and vaccine design for animals - Wu, Yanan; Sun, Zhuoya; Xia, Lu; Tian, Panpan; Jiao, Liuyang; Li, Yanze; Wei, Zhanyong; Wang, Xuannian; Li, Xiaoying; Zhang, Gaiping (Frontiers in Immunology, 2025)
Among various pathogens, viruses pose significant threats to the livestock and poultry industry, resulting in substantial annual costs due to production losses and vaccination. The MHC-I presentation pathway is a crucial surveillance mechanism for preventing viral infections. Consequently, many viruses have evolved sophisticated strategies to inhibit the presentation of viral peptides by MHC-I to CD8+ T-cells, thereby evading the immune system. Understanding the mechanisms that suppress the MHC-I pathway and identifying specific binding peptides are essential for comprehending viral immune evasion and developing effective animal vaccines. This review summarizes the viral strategies for evading immune recognition, including the inhibition of MHC-I molecules synthesis, degradation, transport, and assembly, which affect MHC-I surface expression during viral infections. We also present evidence that MHC-I surface expression is frequently lost during numerous viral infections in livestock and poultry and offer new insights into the underlying mechanisms through which viruses inactivate the MHC-I antigen presentation pathway. Collectively, these advanced findings on viral evasion from the MHC-I pathway could inform the development of more effectives strategies to restore immunological control over viral infections and improve vaccines for the livestock and poultry industry.